Communication research for development : the ISRO experience - Agrawal, Binod C.; Joshi, S. R.; Sinha, Arbind K.; Indian Space Research Organisation. Development and Educational Communication Unit. (Ahmedabad : Development and Educational Communication Unit, Indian Space Research Organisation ; New Delhi : Concept Pub. Co., 1986)
Contributed articles on the evaluation of satellite communication experiment by Indian Space Research Organisation, with special reference to women and youth in India.
Includes index.
Bibliography: p. [59]-80.
Keywords: Television in community development -- India; Television and women -- India; Television and youth -- India; Artificial satellites in telecommunication -- India